The Competency of Pedagogic and Professional of Vocational Teachers in Implementing 21st Century Skill-Based Learning - Yayan Adrianova Eka Tuah; Putu Sudira; Farid Mutohhari; Wahyu Mustafa Kusuma (Universitas Pendidikan Ganesha, 2021)
The pedagogical and professional competence of vocational teachers is still a fundamental question in the education and learning system. In the 21st century, teachers are required to have high pedagogical and professional competencies. This study aims to analyze the extent of the pedagogical and professional competencies of vocational teachers. This research is a descriptive study using a quantitative approach. A total of 232 vocational teachers became respondents in this study. Data were collected through a questionnaire method with an instrument in the form of a 4 Likert scale questionnaire. The data collected were analyzed using descriptive analysis and inferential t-test which includes one-way ANOVA test and independent-sample t-test. The results showed that the pedagogical competence of vocational teachers was in a low category. Meanwhile, the professional competence of vocational teachers is in the high category, but in some indicators, it is still in the low category. Various retraining is needed to improve the pedagogical competence of vocational teachers; meanwhile, psychological approaches must also be taken to improve the professional competence of vocational teachers.